Physicochemical Investigations of Hydrogels Containing Gold Nanoparticles Designed for Biomedical Use - Głąb, Magdalena; Kudłacik-Kramarczyk, Sonia; Drabczyk, Anna; Grabowska, Beata; Tyliszczak, Bożena (Journal of Casting & Materials Engineering, 2021)
Currently, many investigations are being performed to develop dressing materials with a positive effect on the wound healing process. In general, innovative dressings should ensure wound exudate absorption, constitute an external barrier limiting the possibility of wound contamination and, importantly, also provide therapeutic properties. This work is focused on obtaining materials with potential use as dressings for treatment of difficult-to-heal wounds. The synthesis methodology of acrylic hydrogels modified with selected modifiers, i.e. arabic gum, nanogold, bee pollen and chamomile extract, was developed. Next, the sorption properties of the materials were determined as well as their behavior during the incubation in fluids imitating the environment of the human body. Additionally, the impact of such an incubation on their structure was evaluated by FT-IR spectroscopy. It was proved that the modifiers affected the sorption properties of hydrogels, i.e. samples with additives showed even approx. 2.5-fold lower swelling ability. In turn, incubation of hydrogels in simulated body fluids did not cause any rapid changes in pH, which may indicate the biocompatibility of the tested materials with the tested fluids. Thus, it may be concluded that the developed materials show great application potential for biomedical purposes and may be subjected to more advanced studies such as cytotoxicity assessments towards selected cell lines.